Molecular and clinical aspects of oropharyngeal squamous cell carcinoma associated with human papillomavirus - D. Sh. Polatova; A. Yu. Madaminov (Опухоли головы и шеи)
Currently, the role of human papillomavirus (HPV) in carcinogenesis is well known: more than 90 % of HPV-positive oropharyngeal squamous cell carcinomas are caused by HPV type 16 (HPV-16). HPV E6 and E7 oncoproteins play a significant role in the development of this tumor. The E6- mediated degradation of suppressor protein p53 results in G2/M-phase checkpoint dysregulation and inhibition of apoptosis. HPV oncoprotein E7 binds to pRb, promoting its degradation and the release of E2F transcription factor. Diagnostic assays for HPV detection include immunohistochemical staining for p16, polymerase chain reaction, in situ hybridization, and next-generation sequencing. Immunohistochemical examination (determination of p16 protein expression) is an economical and very specific way to detect a viral infection. Patients with HPV-positive oropharyngeal squamous cell carcinoma demonstrate significantly better response to treatment and overall survival rates than those with HPV-negative oropharyngeal squamous cell carcinoma. Despite the fact that five-year overall survival rate in patients with HPV-positive oropharyngeal squamous cell carcinoma after treatment exceeds 80 %, some patients have poor survival. Unfortunately, currently available methods of risk stratification still do not endure their timely identification. Further research is needed to address these problems.